Mesotherapy-Induced Cutaneous Foreign Body-Type Granulomatous Reaction in the Face Treated with Minocycline: Case Report and Literature Review - Zhang Q; Yang L; Yang F; Liu L; Jiang X (Dove Medical Press, 2023)
Qian Zhang,1,* Lihua Yang,1,* Fengjuan Yang,1 Lian Liu,1 Xian Jiang1,2 1Department of Dermatology, West China Hospital, Sichuan University, Chengdu, People's Republic of China; 2Laboratory of Dermatology, Clinical Institute of Inflammation and Immunology, Frontiers Science Center for Disease-Related Molecular Network, West China Hospital, Sichuan University, Chengdu, People's Republic of China*These authors contributed equally to this workCorrespondence: Xian Jiang, West China Hospital, Sichuan University, #37 Guoxue Alley, Wuhou District, Chengdu, Sichuan, 610041, People's Republic of China, Tel +86-028-85423315, Fax +86-028-85422560, Email jiangxian@scu.edu.cnAbstract: Mesotherapy is a popular treatment that delivers substances deep into the skin but induces foreign body-type granulomatous reactions. However, such reactions caused by unauthorized use of topical tranexamic acid products in mesotherapy have never been reported before. We herein demonstrated a case of a 33-year-old woman with multiple mesotherapy-induced foreign body-type granulomas disseminated across her face. The patient was diagnosed with echo-color Doppler (ECD) and successfully treated with medications including minocycline hydrochloride. Then, we reviewed the differential diagnosis and current treatment for foreign body-type granulomatous reaction.Keywords: mesotherapy, foreign body-type granulomatous reaction, tranexamic acid, minocycline, face